2020
DOI: 10.3892/mmr.2020.11208
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chromosomal abnormalities in spontaneous miscarriage by low‑coverage next‑generation sequencing

Abstract: chromosomal abnormalities (cas) can cause spontaneous miscarriage and increase the incidence of subsequent pregnancy loss and other complications. Presently, cas are detected mainly by array comparative genomic hybridization (cGH) and single nucleotide polymorphism microarrays. The present study developed a low-coverage next-generation sequencing method to detect cas in spontaneous miscarriage and assess its clinical performance. in total, 1,401 patients who had experienced an abortion were enrolled in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Chromosomal numerical anomaly is the most common genetic cause of spontaneous miscarriages [33]. Here, 615 cases (81.6%, 615/754) had numerical abnormalities, which is consistent with results from a recent report [34], including 531 cases (45.8%) of single chromosome aneuploidy and 31 (2.7%) cases of multiple aneuploidies (Table 2). The occurrence frequency of each chromosome aneuploidy was analyzed in all 531 cases in this study (Fig.…”
Section: The Associations Between Chromosomal Abnormalities Of Cvss A...supporting
confidence: 91%
“…Chromosomal numerical anomaly is the most common genetic cause of spontaneous miscarriages [33]. Here, 615 cases (81.6%, 615/754) had numerical abnormalities, which is consistent with results from a recent report [34], including 531 cases (45.8%) of single chromosome aneuploidy and 31 (2.7%) cases of multiple aneuploidies (Table 2). The occurrence frequency of each chromosome aneuploidy was analyzed in all 531 cases in this study (Fig.…”
Section: The Associations Between Chromosomal Abnormalities Of Cvss A...supporting
confidence: 91%
“…The recurrence of monosomy X (in 3 cases) in our cohort might be one of the factors in high OR in female CHD cases. Fetuses diagnosed with CHD included cases not surviving to term in which chromosomal abnormalities were considered major causes (∼60% of spontaneous miscarriage) ( Daniely et al, 1998 ; Li et al, 2020 ), and the latest follow-up time of isolated CHD cases were focused on the fetal period (78.43%, 40/51). The aforementioned factors and the characteristics of our cohort led to the OR assessment results which reflect the genetic profile of an unselected sporadic CHD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The results in the present study are similar to those of other studies. 37 , 38 , 39 Some genes in chromosome 16 have been associated with diseases such as thalassemia, 40 prenatal growth retardation, 41 abnormal fetal head circumference 42 and autism. 43 One study found that CNVs on chromosome 16 play an important role in the determination of developmental delay.…”
Section: Discussionmentioning
confidence: 99%